PENGARUH PENERAPAN MODEL MAKE A MATCH TERHADAP HASIL BELAJAR IPS SISWA SD - Aisyah, Maya Nur; Marli, Suhardi; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis purpose of this research to analyze the influence application of the Make A Match model the lerning outcomes of students in learning Social Sciences class V state Primary School 09 West Pontianak. The method used is experimental method with quasi experimental design with Nonequivalent Control Group Design. The population in this research is class V which is 144 students. The sample in this research is VB (experiment class) which is 34 students and class VC (control class) which is 36 students. Based on the result of the calculation of the mean of student learning outcomes (post-test) control class equal to 63.98 and mean of student learning result (post-test) experiment class 76.13 obtained t arithmetic equal to 4.353 and t table α = 5% Of 1.6693, which means t arithmetic > t table (4.353 > 1.6693), then Ha is accepted. From the calculation of effect size obtained 1.02 (high criterion). This means that there is an effect of the application of Make A Match model to the learning outcomes of Social Science of class V state Primary School 09 West Pontianak. Keyword: Influence, Make A Match Model, Learning Outcomes, Social Sciences